Palaeopathology of aboriginal Australians health and disease across a hunter-gatherer continent - Webb, Stephen (Cambridge University Press, 1995)
While their health has suffered enormously because of the arrival of the Europeans, it is assumed that Aboriginal people enjoyed good health before 1788. Using data collected from all parts of the continent, this 1995 book studies the health of Australia's original inhabitants over 50,000 years. It represents the first continental survey of its kind and is the first to quantify and describe key aspects of Australian hunter-gatherer health. The book takes a theoretical approach to Upper Pleistocene regional epidemiology and presents empirical data of the health of late Pleistocene and Holocene populations. Major categories of disease described are: stress, osteoarthritis, fractures, congenital deformations, neoplasms and non-specific and treponemal infections. The author also describes surgical techniques used by Aboriginal people. Offering fresh insight into the study of Australian prehistory and Aboriginal culture, this book will be accessible to specialists and general readers alike. It illuminates the origins of human disease, and will fill a gap in our knowledge of health in the Australasian region.